An Analysis of Human Resource Management Innovation in Private Higher Vocational Colleges under the Background of "Internet +" era - Chen, Junliang (Journal of Theory and Practice of Social Science, 2023)
With the continuous improvement of the development level of Internet + technology, private colleges and universities gradually enter the tide of market economy. In order to better adapt to this change, private higher vocational colleges must actively change and innovate the human resources management mode in the process of development, so as to improve the level of human resources management.